Traffic Light Notification System For Detecting The Emergency Vehicle Using Arduino - Rolie, Amir; Yaacob, Megat (Progress in Engineering Application and Technology, 2022)
The traffic notification was design for helping the traffic flow to go smoother than before. As it will be plant on all the traffic light, it may receive an early information about the arriving emergency transportation that on their way to the destination from about 50 to 100 m from the recent position of that vehicle that time as they will notify by the device that attached on the traffic light. The objective of this production is first to alert traffic about the arriving of the emergency transportation towards the destination. Next, to make sure traffic flow is smooth without having any problem due to many transportation on the road. Then, to increase the safety for all traffic as we can keep the main road clear for a moment. This project is using some combination of component which is Sound sensor, Push Button, LED and Arduino. As we can see, all the traffic will immediately receive a information that are install on the traffic light so they can ready for any possible outcome. In future, we may lead the traffic to give a cooperation to Emergency Vehicle that want to cross the road especially in town. Besides, this project can be receive worldwide.